2022
DOI: 10.1099/jmm.0.001431
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Exophiala dermatitidis is not associated with worse clinical outcomes during acute pulmonary exacerbations in cystic fibrosis

Abstract: Introduction. The black yeast Exophiala dermatitidis has been isolated in respiratory samples from people with cystic fibrosis (CF). However, adequate detection may require longer incubation periods than the current UK national standard for CF respiratory samples. Furthermore, it is unclear whether isolation of E. dermatitidis is associated with poorer clinical outcomes in CF. Hypothesis/gap statement. E. dermatitidis does not cause clinically significant lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…CF patients with higher level of E. dermatitidis IgG antibodies were more often colonized with NTM 23 . It was also reported that CF patients with E. dermatitidis isolation had higher rates of NTM isolation compared to CF patients without E. dermatitidis isolation 24 . Currently, few reports on E. dermatitidis pulmonary infections in non‐CF patients have been published.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CF patients with higher level of E. dermatitidis IgG antibodies were more often colonized with NTM 23 . It was also reported that CF patients with E. dermatitidis isolation had higher rates of NTM isolation compared to CF patients without E. dermatitidis isolation 24 . Currently, few reports on E. dermatitidis pulmonary infections in non‐CF patients have been published.…”
Section: Discussionmentioning
confidence: 99%
“… 23 It was also reported that CF patients with E. dermatitidis isolation had higher rates of NTM isolation compared to CF patients without E. dermatitidis isolation. 24 Currently, few reports on E. dermatitidis pulmonary infections in non‐CF patients have been published. However, it has the potential to increase in the future with the increase in the number of patients with NTM infection.…”
Section: Discussionmentioning
confidence: 99%